Logged On : Smart Government Solutions from South Asia - Bhatti, Zubair K. (Washington, DC: World Bank, 2014)
Logged On looks at mobile and smart phone technology through the lens of good government management. How will developing governments deliver goods and services that citizens care about? How will government in these countries leapfrog over traditional public management reforms to help reach out to and collaborate directly with the citizen? This book provides example after example where this has happened and how mobile technology has helped provide solutions to old problems. Our astounding revelation that mobile technology is helping to fight corruption in Pakistan, improve health delivery in Bangladesh, provide access to government by the ordinary citizen in India, and help monitor elections in Afghanistan. If this Is possible in some place in poor South Asian countries considered the most poor in the world, then how can these examples be spread to further in these counties or in other countries? Logged on provides a look back on conventional solutions that have mostly not worked and why mobile solutions are taking hold. The book offers a model called Smart Proactive Government based on a Feedback model being used in Punjab, Pakistan. The book also offers five solutions that are present in every successful mobile and smart phone example that the authors reviewed.